2022
DOI: 10.1186/s12917-021-03079-2
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and molecular epidemiology investigation of avian hepatitis E in Shandong province, China

Abstract: Background Avian hepatitis E virus (HEV) is the pathogenic agent of big liver and spleen disease (BLS) and of hepatitis-splenomegaly syndrome (HSS) in chickens, which have caused economic losses to the poultry industry in China. In this study, 18 samples of BLS chickens were collected to reveal the molecular epidemiological characteristics of avian HEV in the province of Shandong, China. Results Gross and microscopic lesions of clinical samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Different genotypes of avian HEV have been reported worldwide ( Kwon et al, 2012 ; Liu et al, 2022 ), including strains of different genotypes widely reported in China's Shandong, Jiangxi, and Guangdong Provinces ( Li et al, 2020 ; Liu et al, 2020 ; Su et al, 2020 ; Liu et al, 2022 ). To further determine the molecular characteristics of avian HEV from layer farms and breeder farms, the positive samples were sequenced and analyzed, 14 partial sequences of ORF2 genes of avian HEV strains were obtained, and the genetic evolution showed that all strains except ON457637 and ON457638 belong to the same branch as the potential novel genotypes that we reported earlier, as shown in Figure 1 ( Liu et al, 2022 ), which indicated that potentially novel genotypes might be widespread in some chicken farms in Shandong Province. However, the ON457637 and ON457638 strains were of the same branch as the representative strain of a novel genotype isolated from Gansu Province in 2020 (accession number: MN562265), as reported by Liu et al ( Liu et al, 2020 ), with a nucleotide homology of 91.3% and an amino acid homology of 100%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different genotypes of avian HEV have been reported worldwide ( Kwon et al, 2012 ; Liu et al, 2022 ), including strains of different genotypes widely reported in China's Shandong, Jiangxi, and Guangdong Provinces ( Li et al, 2020 ; Liu et al, 2020 ; Su et al, 2020 ; Liu et al, 2022 ). To further determine the molecular characteristics of avian HEV from layer farms and breeder farms, the positive samples were sequenced and analyzed, 14 partial sequences of ORF2 genes of avian HEV strains were obtained, and the genetic evolution showed that all strains except ON457637 and ON457638 belong to the same branch as the potential novel genotypes that we reported earlier, as shown in Figure 1 ( Liu et al, 2022 ), which indicated that potentially novel genotypes might be widespread in some chicken farms in Shandong Province. However, the ON457637 and ON457638 strains were of the same branch as the representative strain of a novel genotype isolated from Gansu Province in 2020 (accession number: MN562265), as reported by Liu et al ( Liu et al, 2020 ), with a nucleotide homology of 91.3% and an amino acid homology of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype 1 isolates were from Australia and Korea, while genotype 2 had been detected from the United States, Central Europe, and Spain ( Su et al, 2020 ). Genotypes 3 and 4 have been reported in Europe, China and Hungary, Taiwan Province, respectively ( Li et al, 2020 ; Liu et al, 2020 ; Liu et al, 2022 ). In addition, some new genotypes of avian HEV have been reported but not yet categorized ( Liu et al, 2020 ; Su et al, 2020 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Simply P Virus DNA/RNA Extraction Kit (Bioer, Hangzhou, China) was used to obtain the nucleic acid of each sample, following the manufacturer's instructions. In our previous study, the PCR primers of CAV, fowl adenovirus (FAdV), reticuloendotheliosis virus (REV), avian leukosis virus (ALV), Marek's disease virus (MDV), and avian hepatitis E virus (HEV) were reported [12]; primer sequences are shown in Table 1. The total volume of the reaction system was 25 µL.…”
Section: Viral Dna Detection By Pcrmentioning
confidence: 99%
“…The chickens had severe hepatosplenomegaly syndrome, many bleeding spots, and apparent bleeding clots in the livers ( 16 ). In 2022, a study described cases of aHEV associated with hepatosplenomegaly, rupture, and hemorrhage from several cities in Shandong ( 17 ).…”
Section: Introductionmentioning
confidence: 99%